Gambaran Computed Tomografi Scan Toraks Teratoma Kistik Paru - DETI NURBAETI; AZIZA G ICKSAN; HERIAWATY HIDAYAT (Indonesian Journal of Cancer, 2014)
Pulmonary cystic teratoma is a very rare disease, composed of tissues from more than one germ cell line. Pulmonary cystic teratoma commonly involve the upper lobe of the left lung, most follow a benign course and are incidental findings during routine chest X-rays. Proper diagnosis is needed to determine adequate treatment in order to reduce symptoms and improve quality of life. We report a twenty six years old man with clinical symptom hemoptysis, chest pain and dyspnea since one month before admission. The chest X-ray showed a large opacity of the entire right hemithorax, there is no calcification. On enhanced chest CT examination, we found an encapsulated cystic mass on the upper and middle of the right lung with peripheral enhancement. Histopathological examination confirmed an infected cyst with cystic teratoma. The main purpose of this report is to emphasize the importance of enhanced chest CT in evaluating patient suspected pulmonary cystic teratoma.